2014
DOI: 10.1103/physrevlett.112.095003
|View full text |Cite|
|
Sign up to set email alerts
|

Alfvénic Propagation: A Key to Nonlocal Effects in Magnetized Plasmas

Abstract: A long-standing puzzle in fusion research comes from experiments where a sudden peripheral electron temperature perturbation is accompanied by an almost simultaneous opposite change in central temperature, in a way incompatible with local transport models. This Letter shows that these experiments and similar ones are fairly well quantitatively reproduced, when induction effects are incorporated in the total plasma response, alongside standard local diffusive transport, as suggested in earlier work [Plasma Phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Initial conditions were randomly sampled from a thermal distribution, i.e., E 0 and r picked up respectively from a zero-mean, unit-variance normal distribution, and from the uniform distribution in (0, 1), and The threshold condition a = 1 places a constraint upon the wave amplitude which is often difficult to satisfy in laboratory (and sometimes also astrophysical) plasmas, where fluctuations are ordinarily small with respect to mean fields. Although it is not relevant to the present work, we mention that recently we showed that this threshold is not always needed, since under some conditions it can be traded for a threshold upon the duration of the wave-particle interaction, in a way reminiscent of quantum-mechanics indeterminacy relations: see the paper [20]…”
Section: Methodsmentioning
confidence: 99%
“…Initial conditions were randomly sampled from a thermal distribution, i.e., E 0 and r picked up respectively from a zero-mean, unit-variance normal distribution, and from the uniform distribution in (0, 1), and The threshold condition a = 1 places a constraint upon the wave amplitude which is often difficult to satisfy in laboratory (and sometimes also astrophysical) plasmas, where fluctuations are ordinarily small with respect to mean fields. Although it is not relevant to the present work, we mention that recently we showed that this threshold is not always needed, since under some conditions it can be traded for a threshold upon the duration of the wave-particle interaction, in a way reminiscent of quantum-mechanics indeterminacy relations: see the paper [20]…”
Section: Methodsmentioning
confidence: 99%